Implementation of the Creative Problem Solving (CPS) Learning Model Based on Information and Communicaton Technologies (ICT) to Improve Mathematics Learning Outcomes - Nisa Miftachurohmah; Nasruddin Nasruddin; Jahring Jahring; Agus Sugiarto; Putri Tipa Anasi; Syarifuddin Syarifuddin; Andri Estining Sejati (IKIP Mataram, 2022)
This research aims to improve students' mathematics learning outcomes by using a learning model based on Information and Communicaton Technologies (ICT). This research is a Classroom action research qualitative research. This research method consists of: (1) planning (planning); (2) the implementation of the action (action); (3) observation and evaluation (observation and evaluation); (4) reflection (reflection). This research uses descriptive statistical data analysis involving 20 students, including 7 boys and 13 girls and using instruments in the form of student worksheets and interview guidelines for teachers and students. Based on the results of initial observations, it shows that the low learning outcomes obtained by students. This is because teachers have less ability to vary learning models/strategies, where teachers only explain the material to students and then ask questions, but only a few students have an active understanding of concepts/knowledge in learning. Based on the daily test results, before the first cycle of action, only 40% of students with an average score of 60.1 scored 70 from the KKM (Minimum Graduation Criteria), which was 75%. In the first cycle, there was an increase from the initial test which was 40% to 55% of students with an average score of 65.98 who obtained a score of 70, while in the second cycle the test also increased to 85% with an average score of 80.56 who obtained a score 70. The final result of this research is that it can improve Mathematics Learning Outcomes by Applying the ICT-based Creative Problem Solving (CPS) Learning Model.